2015
DOI: 10.1105/tpc.15.00385
|View full text |Cite
|
Sign up to set email alerts
|

PLANT U-BOX PROTEIN10 Regulates MYC2 Stability in Arabidopsis

Abstract: MYC2 is an important regulator for jasmonic acid (JA) signaling, but little is known about its posttranslational regulation. Here, we show that the MYC2 C-terminal region interacted with the PLANT U-BOX PROTEIN10 (PUB10) armadillo repeats in vitro. MYC2 was efficiently polyubiquitinated by PUB10 with UBC8 as an E2 enzyme and the conserved C249 in PUB10 was required for activity. The inactive PUB10(C249A) mutant protein retained its ability to heterodimerize with PUB10, thus blocking PUB10 E3 activity as a domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 58 publications
2
92
0
Order By: Relevance
“…In all these cases, MYC protein degradation was mediated by the proteasome. Recently, it was shown that MYC2 is polyubiquitinated by PLANT U-BOX PROTEIN10 (PUB10), which belongs to the U-box family of E3 ligases (Jung et al, 2015). There thus is growing evidence that the JA pathway is tightly coordinated with other environmental inputs and that part of this regulation operates at the translational level.…”
Section: Discussionmentioning
confidence: 99%
“…In all these cases, MYC protein degradation was mediated by the proteasome. Recently, it was shown that MYC2 is polyubiquitinated by PLANT U-BOX PROTEIN10 (PUB10), which belongs to the U-box family of E3 ligases (Jung et al, 2015). There thus is growing evidence that the JA pathway is tightly coordinated with other environmental inputs and that part of this regulation operates at the translational level.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a total of 134 potential candidate genes were identified in 200‐kb genomic regions among the 14 association signals. Some genes associated with cell division or elongation, plant hormone metabolisms, proteins modification or degradation and signalling or transport of specific proteins, have been found to participate in the regulation of PH in soybean (Jung et al, ; Ubeda‐Tomas & Bennett, ; Wang, Zhao, et al, ; Yao et al, ; Zhong et al, ). To further identify the candidate genes that regulated PH, haplotype analysis of candidate genes was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The basic helix–loop–helix (bHLH) transcription factor MYC2 has emerged in recent years as a master regulator of many aspects of the JA signalling pathway and as a key point of cross‐talk between the signalling pathways of JA and other phytohormones, such as ABA, SA, gibberellins (Gas) and auxin (IAA) (Kazan and Manners, ). A recent report has shown that MYC2 is targeted by the U‐box‐type E3 ubiquitin ligase PUB10 for ubiquitination and subsequent degradation during the JA response (Jung et al ., ), suggesting that PUB10 negatively regulates the JA signalling pathway. However, the plant immunity‐related phenotype on the PUB10 loss‐of‐function and PUB10‐overexpressing plants was not characterized in the report.…”
Section: U‐box Typementioning
confidence: 99%